An epidemiological qualitative/quantitative SWOT‐AHP analysis in order to highlight the positive or critical aspects of dental implants: A pilot study - Silvana Mirella Aliberti; Richard H. W. Funk; Marco De Stefano; Thomas Hoffmann; Mario Capunzo (Wiley, 2024)
Abstract Objectives In recent years, dental implants are increasing in popularity due to their high success rate, demonstrated functionality, and aesthetic treatment results. Scientific research is very active in proposing improvements in the quality and survival of implants, taking into consideration various aspects. The objective of this study was to provide a holistic epidemiologic view of the state of dental implants, using a systematic approach based on a multimethod SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis and AHP (analytical hierarchical process) qualitative-quantitative analysis to identify the characteristics that can determine their success or failure. Materials and Methods The study used the hybrid method of SWOT‐AHP. Results Analysis of the results showed that among strengths, the skill of the dentist was considered the most important factor, followed by the success of dental implants in the old people; among weaknesses, bruxism and chronic diseases were highlighted; for opportunities, biomechanical behavior, in terms of good mechanical strength and good tribological resistance to chemical and physical agents in the oral cavity, were considered the most important factors; finally, among threats, medical liability and biomechanical problems had equal weight. Conclusions This study applied a multimethod SWOT‐AHP approach to bring out favorable or critical evidence on the topic of dental implants. In accordance with the result of the strategic vector identified in the Twisting zone Adjustment type section, showed that implant surgery is a widespread technique but always needs improvement to increase the likelihood of success and reduce the complications that can lead to implant failure.